1928
DOI: 10.1002/j.1551-8833.1928.tb13661.x
|View full text |Cite
|
Sign up to set email alerts
|

Succinchlorimide for the Treatment of Small Quantities of Potable Water

Abstract: The purpose of the work here reported was to find, if possible, a water disinfectant suitable for small scale preparation of potable water that would be an improvement on the disinfectant used in the present official Army method for the preparation of potable water in the field. The work to date is reported because of the appointment of a joint board representing both the Chemical Warfare Service and the Medical Department to continue. that search. HISTORICAL A full account of the development of the various me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…30 A major current use for bromochlorodimethylhydantoin (BCDMH) is in biofouling control in cooling towers. 51 In a study conducted to compare the relative effectiveness of BCDMH Downloaded by [University of Calgary] at 12:41 04 February 2015 NCS was shown to be bactericidal by Wood 78 and later by Reddish and Pauley. 79 It has been reported that NCS at a total chlorine concentration of 1.5 mg/€ is effective as a bactéricide in water containing high chlorine demand against Salmonella typhosa, E. coli, and Shigella dysenteriae, with a contact time of between 5 and 10 min at temperatures ranging between 2 and 27°C.…”
Section: B Efficacies Of Current N-halaminesmentioning
confidence: 98%
“…30 A major current use for bromochlorodimethylhydantoin (BCDMH) is in biofouling control in cooling towers. 51 In a study conducted to compare the relative effectiveness of BCDMH Downloaded by [University of Calgary] at 12:41 04 February 2015 NCS was shown to be bactericidal by Wood 78 and later by Reddish and Pauley. 79 It has been reported that NCS at a total chlorine concentration of 1.5 mg/€ is effective as a bactéricide in water containing high chlorine demand against Salmonella typhosa, E. coli, and Shigella dysenteriae, with a contact time of between 5 and 10 min at temperatures ranging between 2 and 27°C.…”
Section: B Efficacies Of Current N-halaminesmentioning
confidence: 98%